CRIMINAL LEGAL POLICY ON SEXUAL VIOLENCE AND LEGAL PROTECTION FOR VICTIMS OF SEXUAL VIOLENCE (Study of Medan District Court Decision Number 1170/Pid.Sus/2018/PN/Mdn and Medan District Court Decision Number 1853/Pid.B/2019/PN.Mdn) - Susila, Ayu Hutami; Ablisar, Madiasa; Yunara, Edi; Bariah, Chairul (Inspiring Law Journal, 2024)
Sexual violence in Indonesia is an increasingly urgent case, with 431,471 cases recorded in 2020, including 3,602 cases in the public domain. Sexual violence is defined as a physical or non-physical sexual act by someone who has power over the victim, without the victim's consent. Its forms include harassment, exploitation, forced contraception, abortion, rape, marriage, prostitution, slavery, and sexual torture. This thesis discusses the legal formulation of the crime of sexual violence, legal protection for victims, and an analysis of the Medan District Court's decision regarding cases of sexual violence. Using normative legal research methods, this study examines existing regulations, including the Criminal Code, Law No. 23/2004 concerning Domestic Violence, the Bill on the Elimination of Sexual Violence, Law No. 39/1999 concerning Human Rights, the Universal Declaration of Human Rights, and Law No. 13/2006 concerning Protection of Witnesses and Victims, which regulate criminal acts and protection of victims of sexual violence.